SQL Server 2005 DBA street smarts : - Jorden, Joseph L. (Wiley Pub., 2007)
HE STREET SMARTS SERIES is designed to help current or sparing IT professionals put their certification to work for them. Full of practical, real world scenarios, each book features actual tasks from the field and then offers step-by-step exercises that teach the skills necessary to complete those tasks. And because the exercises are based upon exam objectives from leading technology certifications, each Street Smarts book can be used as a lab manual for certification prep.